Impact of COVID-19 Pandemic on Incidence and Prevalence of Cough and its Types: A Real-world Study - Vora, Agam; Jindal, Surinder Kumar; Thakor, Priti; Malve, Harshad; Panchal, Roshni (Journal of the Association of Physicians of India, 2025)
Cough is a prominent symptom in both the acute and postinfective phases of coronavirus disease 2019 (COVID-19). This retrospective study examined the prevalence and clinical characteristics of acute cough before, during, and after COVID-19. The anonymized electronic medical records (EMR) data of the pediatric, adult, and elderly patients with cough complaints from 2017 to 2023 was analyzed. Before, during, and after the pandemic, adults accounted for a higher proportion of the patient population with acute cough than the other two age-groups. Among the specialties, consultant physicians (CPs) and general physicians (GPs) were frequently consulted. When the cough type was analyzed, unspecified cough was the most common before and during COVID-19 in all three age categories, which continued even after the pandemic. The age-wise distribution of the cough prevalence till 2023, with 2020 as the base year, also showed unspecified cough as the most common in all three age-groups. Nonproductive cough was prevalent among adult and pediatric age-groups, while productive cough occurrence was more frequent in the elderly. Upon comparing the prevalence of cough during and after the pandemic, there was an increase in the overall occurrence of cough, with the unspecified cough being the most. In the age-wise comparison of the cough prevalence pre- and post-COVID-19, adult patients had the highest prevalence of all three cough types, followed by elderly patients. Pediatric patients had the lowest cough prevalence. A significant increase in the incidence of acute cough post-COVID-19 highlights the complex and long-term respiratory consequences of COVID-19. The higher prevalence of unspecified cough suggests the need for cough categorization and adapting efficient documentation to ensure holistic management of cough.